Performance Understanding and Learning System (PULSE-KEY): development of a framework for implementation and performance evaluation of healthcare delivery models of care - Katrina L Campbell; Rumbidzai N Mutsekwa; Russell Canavan; Rebecca L Angus; Joshua Byrnes; Liza-Jane McBride (BMJ Open)
Objectives Efficient performance evaluation is essential for driving improvement, ensuring accountability and optimisation of outcomes in healthcare delivery. However, its complexity often leads to ineffective implementation. This article aims to advance the field of performance measurement within alternative healthcare delivery models of care through the development and validation of a comprehensive evaluation framework.Design and participants A seven-stage methodological approach was adapted from the Health Care Quality Indicators Project and a conceptual analysis method. The first three stages, which have been previously published, included: (1) an extensive literature review, (2) engagement with consumers and patients through interviews and a discrete choice experiment and (3) involvement of stakeholders across the healthcare system via interviews and surveys. Building on this previous work, the present study advances the framework development through four additional stages: (4) development of a conceptual framework (identifying, categorising, synthesising concepts into outcome domains), (5) expert consultation, (6) validation using a real-world case study and (7) refinement for practical applicability and effectiveness in evaluating alternative healthcare delivery models of care.Results The framework was developed by synthesising insights from phases 1–3 of our previously published work and refined through consultations with 25 experts, confirming its relevance, clarity and suitability for diverse audiences. This study also details the framework’s validation, refinement and finalisation process. The final framework is structured around eight primary domains, covering implementation outcomes, effectiveness, safety, patient-centredness, healthcare provider experience, access, service delivery and economic evaluation. Within the implementation outcomes domain, three subdomains—adoptability, implementability and sustainability—are further delineated, providing a comprehensive assessment.Conclusions The comprehensive evaluation framework developed in this study provides a vital tool for enhancing implementation and performance measurement in alternative healthcare delivery models. By integrating insights from various stakeholders, the framework promotes data-driven decisions on adopting, implementing and sustaining various healthcare delivery models. Through systematic application, this framework aims to drive tangible enhancements in patient outcomes, improve healthcare provider experiences, and optimise overall healthcare system efficiency.